L'imaginaire du démoniaque dans la Septante Une analyse comparée de la notion de "démon" dans la Septante et dans la Bible Hébraïque - Angelini, Anna (Supplements to the Journal for the Study of Judaism, 2021)
This book offers a thorough analysis of demons in the Hebrew Bible and Septuagint in the wider context of the ancient Near East and the Greek world. Taking a fresh and innovative angle of enquiry, Anna Angelini investigates continuities and changes in the representation of divine powers in Hellenistic Judaism, thereby revealing the role of the Greek translation of the Bible in shaping ancient demonology, angelology, and pneumatology. Combining philological and semantic analyses with a historical approach and anthropological insights, the author both develops a new method for analyzing religious categories within biblical traditions and sheds new light on the importance of the Septuagint for the history of ancient Judaism.